1997
DOI: 10.1017/s0022029996001999
|View full text |Cite
|
Sign up to set email alerts
|

Management practices associated with high mortality among preweaned dairy heifers

Abstract: In a national survey of US dairy operations, 1685 dairy operations reported 47057 new dairy heifers (either births or acquisitions) and 4427 deaths (9·4%) of preweaned dairy heifer calves over a 3 month period. Stepwise logistic regression was used to identify management practices associated with high mortality among preweaned heifers in dairy operations where at least three dairy heifer calves were born alive or moved on to the operation. Analysis was done twice: once by separating all operations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 20 publications
2
47
0
6
Order By: Relevance
“…The mortality rate for this group of artificially reared H-F and J calves was low compared with those reported in other studies (Losinger and Heinrichs, 1997;Svensson et al, 2006;Lombard et al, 2007;Gulliksen et al, 2009). However, morbidity -and in particular, incidents of BRD -was greater in this study than that generally observed for artificially reared dairy calves (Svensson et al, 2003;Lundborg et al, 2005;Gay and Barnouin, 2009).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The mortality rate for this group of artificially reared H-F and J calves was low compared with those reported in other studies (Losinger and Heinrichs, 1997;Svensson et al, 2006;Lombard et al, 2007;Gulliksen et al, 2009). However, morbidity -and in particular, incidents of BRD -was greater in this study than that generally observed for artificially reared dairy calves (Svensson et al, 2003;Lundborg et al, 2005;Gay and Barnouin, 2009).…”
Section: Discussionmentioning
confidence: 51%
“…Dairy calf mortality rates vary among countries, with estimates as low as 3.1% being reported in Sweden and Denmark (Svensson et al, 2006;Gulliksen et al, 2009), and rates ranging from 7.9% to 9.4% reported in the United States (Losinger and Heinrichs, 1997;Lombard et al, 2007). In Ireland, the mortality rate for dairy calves during the first year of life is high, at 7.5% (DAFM, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Other factors affecting calf and heifer mortality include region, herd and group size, birth type, average herd milk production level, availability of colostrums, season of birth, sex of calf and dams' parity (e.g. Losinger and Heinrichs, 1997;Svensson et al, 2006;Gulliksen et al, 2009). Among the few genetic studies Hansen et al (2003) analyzed genetic parameters of postnatal mortality of Danish Holstein calves aged up to 180 days using linear models.…”
Section: Introductionmentioning
confidence: 99%
“…Mortality of dairy cows has been reported in the range of 3.5 to 6.1% in previous studies conducted in different countries (Thomsen et al, 2004;McConnel et al, 2008;Raboisson et al, 2011;Alvåsen et al, 2014), mortality of youngstock has been reported from 2.4 to 9.4% (Losinger and Heinrichs, 1997;Gulliksen et al, 2009;Bleul, 2011;Azizzadeh et al, 2012, Santman-Berends et al, 2014. Previous studies have identified several animal level risk factors associated with dairy cow mortality hazard, e.g.…”
Section: Introductionmentioning
confidence: 99%